DMSO Alleviates LPS-Induced Inflammatory Responses in RAW264.7 Macrophages by Inhibiting NF-κB and MAPK Activation - Hyunju Han; Jin-Kyu Kang; Keun Jae Ahn; Chang-Gu Hyun (MDPI AG, 2023)
Dimethyl sulfoxide (DMSO), an amphipathic molecule composed of one highly polar sulfinyl group and two nonpolar methyl groups, is considered an excellent solvent due to its capability to dissolve many polar and nonpolar compounds. Therefore, DMSO is widely used to solubilize drugs for therapeutic applications. DMSO is reported to possess anti-inflammatory, anticancer, and antioxidative capacities, and the anti-inflammatory efficacy of DMSO has been intensively studied in various cell lines and animal models. An in vitro model of mouse macrophage RAW 264.7 cells has been widely used, among several experimental designs, for evaluation during the development of new anti-inflammatory drugs. DMSO, which is used to dissolve samples, is also prone to experimental errors because of its anti-inflammatory properties. Therefore, we systematically confirmed the cytotoxic and anti-inflammatory effects of DMSO and the related signaling pathways in RAW 264.7 cells. The results show that DMSO at 0.25% to 1.5% did not result in cellular toxicity, with results comparable to the control group where DMSO is absent; at concentrations 2.0%, however, it inhibited the viability of RAW264.7 cells (13.25%). The results demonstrate that pretreatment with DMSO profoundly attenuates the lipopolysaccharide (LPS)-stimulated levels of nitric oxide (NO) and prostaglandin (PG)E2, as well as the levels of pro-inflammatory cytokines, cyclooxygenase-2 (COX-2) protein, and inducible nitric oxide synthase (iNOS). Collectively, the DMSO pretreatments appear to notably alleviate LPS-induced damage by reducing phosphorylation of p38, c-Jun N-terminal kinase (JNK), and extracellular signal-regulated kinase proteins (ERKs), nuclear factor-kappa-B (NF-κB) in addition to NF-κB/p65 nuclear translocation. Taken together, the results clearly show that DMSO attenuates the inflammatory response in LPS-induced RAW264.7 cells by regulating the activation of the MAPK and NF-κB signaling pathways. These results contribute to potentially reducing experimental errors or misjudgments when using the LPS-induced RAW 264.7 macrophage cell model for evaluation during the development of new anti-inflammatory drugs.